2020
DOI: 10.3390/v12070696
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-99a Restricts Replication of Hepatitis C Virus by Targeting mTOR and De Novo Lipogenesis

Abstract: In this study, we investigated the role of microRNA-99a (miR-99a) in hepatitis C virus (HCV) replication and lipogenesis in hepatocytes. Cell-culture-derived HCV (HCVcc) infection caused down-regulation of miR-99a in Huh-7 cells, and the relative levels of miR-99a were significantly lower in the sera of the HCV-infected patients than in those of healthy controls. Transfection of miR-99a-5p mimics resulted in a decrease in the intracellular and secreted HCV RNA levels. It also caused a decreased mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Previous studies have revealed that miR-99a functions by targeting on mammalian target of rapamycin (mTOR) 19 , 27 and that mTOR is a pivotal regulator of T cell differentiation and glycolysis. 24 , 28 We therefore explored whether mTOR is involved in miR-99a-regulated CD4 + T cell differentiation and glycolysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that miR-99a functions by targeting on mammalian target of rapamycin (mTOR) 19 , 27 and that mTOR is a pivotal regulator of T cell differentiation and glycolysis. 24 , 28 We therefore explored whether mTOR is involved in miR-99a-regulated CD4 + T cell differentiation and glycolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that miR-99a functions by targeting the mRNAs of genes, such as mTOR, NOX4, HOXA1, and KDM6B. 19 , 27 , 38 , 39 , 40 Among those target genes, mTOR is well-known to regulate CD4 + T cell differentiation and glycolysis. 24 , 28 Consistently, our bioinformatics analysis showed that mTOR was a target for miR-99a in CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-99a was significantly lower in patients with chronic HCV infection than in healthy subjects. miR-99a modulates the expression of the mammalian target of rapamycin protein (mTOR) to improve intracellular lipid accumulation and limit HCV replication [ 57 ]. miR-200c, which is increased in HCV-infected patients, regulates the Src kinase signaling pathway and promotes liver fibrosis by directly targeting Fas-associated phosphatase 1 (FAP-1), a negative regulator of Src signaling [ 60 ].…”
Section: Association Of the Causes Of Liver Cirrhosis And Mirnasmentioning
confidence: 99%
“…The signal transducer and activator of transcription (STAT) signaling pathways play an important role in viral infection, such as immune regulation and apoptosis 18,19 . The mammalian target of rapamycin (mTOR) signaling pathway is one of the major cell signaling pathways in viral infection 20,21 . The aim of the present study is to validate how DAPP inhibit EV71 to induce the apoptosis of Vero cell and provide a potential pharmaceutical against the infection of EV71 virus.…”
Section: Introductionmentioning
confidence: 98%